GAMBARAN PERILAKU PHUBBING PADA SISWA MENENGAH ATAS (SMA) - Maharani, Violanisa; Nurfarhanah, Nurfarhanah; Netrawati, Netrawati; Izzati Adlya, Soeci (Penerbit Lafadz Jaya, 2025)
This study aims to describe the phubbing behavior among Senior High School students. Phubbing is the act of ignoring a conversation partner by focusing more on using a smartphone, which results in a decline in the quality of social interactions. This research was motivated by the widespread use of smartphones among students, which has the potential to shift their attention away from face-to-face communication. The research method used is descriptive quantitative, with the population consisting of all students of SMA Negeri 1 Padang, and a sample of 274 students selected using proportional simple random sampling. The research instrument was a phubbing behavior questionnaire developed based on four factors: nomophobia, interpersonal conflict, self-isolation, and problem acknowledgment. Data were analyzed using descriptive statistics to determine categories and score distributions.The results showed that overall, students’ phubbing behavior was in the high category, with a mean percentage of 66.56%. The nomophobia factor had a mean percentage of 68.86% (high category), interpersonal conflict 72.77% (high category), self-isolation 58.02% (medium category), and problem acknowledgment 65.85% (medium category). These findings indicate that anxiety about being separated from smartphones and avoiding conflict are the dominant factors influencing students’ phubbing behavior. The conclusion of this study is that phubbing behavior among students of SMA Negeri 1 Padang is quite concerning because it affects the quality of students’ social relationships. Therefore, it is recommended that guidance and counseling teachers provide information services, individual counseling, and group counseling to increase students’ awareness, develop communication skills, and reduce smartphone dependency.